Effects of ketamine administration on mTOR and reticulum stress signaling pathways in the brain after the infusion of rapamycin into prefrontal cortex - Abelaira, Helena M. (2017)
Recent studies show that activation of the mTOR signaling pathway is required for the rapid antide- pressant actions of glutamate N-methyl-D-aspartate (NMDA) receptor antagonists. A relationship be- tween mTOR kinase and the endoplasmic reticulum (ER) stress pathway, also known as the unfolded protein response (UPR) has been shown. We evaluate the effects of ketamine administration on the mTOR signaling pathway and proteins of UPR in the prefrontal cortex (PFC), hippocampus, amygdala and nucleus accumbens, after the inhibiton of mTOR signaling in the PFC. Male adult Wistar rats received pharmacological mTOR inhibitor, rapamycin (0.2 nmol), or vehicle into the PFC and then a single dose of ketamine (15 mg/kg, i.p.). The immunocontent of mTOR, eukaryotic initiation factor 4E-binding protein 1 (4E-BP1), eukaryotic elongation factor 2 kinase (eEF2K) homologous protein (CHOP), PKR-like ER kinase (PERK) and inositol-requiring enzyme 1 (IRE1) e alpha were determined in the brain. The mTOR levels were reduced in the rapamycin group treated with saline and ketamine in the PFC; p4EBP1 levels were reduced in the rapamycin group treated with ketamine in the PFC and nucleus accumbens; the levels of peEF2K were increased in the PFC in the vehicle group treated with ketamine and reduced in the rapamycin group treated with ketamine. The PERK and IRE1-alpha levels were decreased in the PFC in the rapamycin group treated with ketamine. Our results suggest that mTOR signaling inhibition by rapamycin could be involved, at least in part, with the mechanism of action of ketamine; and the ke- tamine antidepressant on ER stress pathway could be also mediated by mTOR signaling pathway in certain brain structures.